Inequality, individualism, and overwork - Till van Treeck (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
It can be argued that the rich world has long reached the social limits to growth, which were presciently seen by key figures in post-Keynesian economics. Reducing working hours, therefore, may have a greater potential to increase people's life satisfaction than more economic growth. One of the obstacles to a reduction in working hours is the 'rat race' for relative income. The rat race is exacerbated by high wage inequality, weak collective bargaining institutions, and low quality of public services. Results from a representative survey of German workers show that, despite the rat race, public support for measures to reduce working hours, such as the four-day week or a social service period, is high in Germany. Compared to the United States, the German political economy still can be characterized as a coordinated market economy, in which wage inequality is lower, collective bargaining plays a larger role, and public services are more universal.
Keywords: J22; D31; B5; 330; Inequality; Working time preferences; Social limits to growth; Post-Keynesian economics